Percetakan Al-Qur’an Palembang 1848 dalam Lintasan Budaya Cetak Abad ke-19 - Subhan, Ahmad (SUHUF, 2021)
This article describes some aspects which become the background of the emergence of the printing press of Kemas Muhammad Azhari which printed the Qur’an using stone printing equipment or lithography. The phenomenon of Bumiputra printing in Palembang in the colonial era that emerged in 1848, the author examines with the the approach of book history approach, printed culture, and an explanation of the acceptance of printing technology by Muslims. As a European creation technology, lithography is more accepted by Muslims than typography. This acceptance occurred massively in the mid-19th century as colonialism strengthened and the reach of the traveler clergy as agents of print culture in evangelizing missions expanded. Cultural contacts in the form of technological transmission between European printed cultural agents and Indian as well as Southeast Asian Muslims gave rise to the printing industry in the British colonies and the Dutch East Indies. Muhammad Azhari Kemas printing press was the result of the trajectory of the pilgrimage and Christian missionary missions that cross the Malacca Strait as a shipping route where Singapore was the crossing point.